2005
DOI: 10.3758/bf03192742
|View full text |Cite
|
Sign up to set email alerts
|

Measuring health beliefs on the Internet: A comparison of paper and Internet administrations of the Multidimensional Health Locus of Control Scale

Abstract: A growing number of studies have supported the use of unidimensional psychometric test instruments administered via the Internet; however, support for the use of multidimensional scales is weak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 51 publications
4
44
0
Order By: Relevance
“…Several studies have shown that some instruments maintain their psychometric properties when adapted to the internet, when compared to the traditional paper-and-pencil format (Bates & Cox, 2008;Bressani & Downs, 2002;Fish et al, 2010;Herrero & Meneses, 2006;Hewson & Charlton, 2005;McCabe et al, 2005;Meyerson & Tryon, 2003;Thorndike et al, 2009). However, several other reports have shown that the reliability, validity and factor structure of instruments adapted to the internet were not equivalent to the observed in paper-and-pencil applications (Buchanan et al, 2005;Finegan & Allen, 1994;Hedman et al, 2010;Im et al, 2005;Luce et al, 2007;Naus et al, 2009;Suris et al, 2007;Whitener & Klein, 1995).…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Several studies have shown that some instruments maintain their psychometric properties when adapted to the internet, when compared to the traditional paper-and-pencil format (Bates & Cox, 2008;Bressani & Downs, 2002;Fish et al, 2010;Herrero & Meneses, 2006;Hewson & Charlton, 2005;McCabe et al, 2005;Meyerson & Tryon, 2003;Thorndike et al, 2009). However, several other reports have shown that the reliability, validity and factor structure of instruments adapted to the internet were not equivalent to the observed in paper-and-pencil applications (Buchanan et al, 2005;Finegan & Allen, 1994;Hedman et al, 2010;Im et al, 2005;Luce et al, 2007;Naus et al, 2009;Suris et al, 2007;Whitener & Klein, 1995).…”
Section: Introductionmentioning
confidence: 82%
“…Unfortunately, factorial invariance between different deployment formats has not been evaluated in only but a few studies comparing equivalence of scales (see e.g. Fish et al, 2010;Herrero & Meneses, 2006;Hewson & Charlton, 2005;Thorndike et al, 2009). The fact that factor structure invariance may not be present in different formats of psychometric scales has been acknowledged in several similar studies comparing paper-andpencil, internet and telephone interview filling methods (Carlbring et al, 2007;Hedman et al, 2010;Naus et al, 2009;Suris et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations